Legal protection against dental Service recipient patients reviewed from law number 36 year 2009 about health in Demak district - Yoghi Bagus Prabowo; Agnes Widanti S; Irma Haida (SOEPRA, 2019)
Tukang Gigi Is Worker In Tradisional Dental Health Service. The Law No. 36/2009 Has Explained The Differences Between Health Workers And Traditional Health Workers. The Objective Of This Study Is To Determine The Legal Protection For The Patients Treated By The Tukang Gigi. The Research Method Used In This Study Was Sociological Juridical Approach With Analytic Descriptive Specification. The Respondents Of This Study Were 4 Licensed And 9 Unlicensed Tukang Gigi With 10 Patients, Respectively. Meanwhile, The Expert In This Study Was The Head Of Health Office Of Demak Regency And The Head Of Consumer Supervision And Protection Board (Lp2k) Of The Central Java Province.The Results Of This Study Showed That 9 Unlicensed And 1 Licensed Tukang Gigi In Demak Had Done Unauthorized Jobs. The Results Also Showed That 70% Of Patients Expressed Dissatisfaction With Their Dental Services. Those Patients Have The Right To Get Legal Protection For Services Provided By Tukang Gigi. Tukang Gigi Has The Legal Responsibility In Doing Their Works. Tukang Gigi Who Do The Unauthorized Jobs Lead To Their Legal Responsibilities—Including Civil, Criminal, And Administrative—For Their Dental Services